Integration of Economic Order Quantity (EOQ) Method and Min-Max Stock Method in Controlling Raw Material Inventory in The Furniture Industry: Integrasi Metode Economic Order Quantity (EOQ) Dan Metode Min-Max Stock Dalam Pengendalian Persediaan Bahan Baku Pada Industri Furniture - Hakiki, Gema Fajar; Jakaria, Ribangun Bamban (Universitas Muhammadiyah Sidoarjo, 2023)
Indonesia is a country with a very rapidly developing economy in the manufacturing sector that produces furniture products. The existence of fierce competition between companies and the limited supply of raw materials makes the need for raw materials in the production process uncontrollable so that the desired goals of the company cannot be achieved. One of the factors that greatly influences is regarding the problem of raw material inventory levels. The issue of raw materials is very important for an enterprise because it has a great influence on the profit obtained.Economic Order Quantity (EOQ) and Min-Max Stock methods are carried out to control raw material inventories resulting in savings with optimal purchases by not experiencing inventory shortages.This research is expected so that waste and inventory that are too small can be known at intervals of time to be more effective and efficient in the production process.From the results of analysis and data processing, it can be seen that the number of orders for sonokeling wood raw materials needs is 17.670 m3 and amara wood raw materials are 4.325 m3 with an order frequency of 1 time and an ordering cycle distance of 33 days. So the delay in raw material inventory is influenced by several factors, namely the purchase price of wood raw materials, estimates in using raw materials, purchasing policies from companies and government policies related to regulations with the Multistakeholder Timber Verification and Legality System (SLVK) for inventory control are still lacking.